Longer Telomere Length and its Association with Lower Levels of C-Peptide - Yang, Min; Jiang, Ping; Jin, Chenghao; Wang, Jinshan (Frontiers in Endocrinology, 2017)
Background: Telomeres undergo shortening with each cell division, which could be accelerated by increase obesity and is also related to endocrinology systems. In this study, we aimed to examine the complex association between telomere, C-peptide, and obesity as well as chronic inflammation in a large population-based cross-sectional survey. Methods: We used data from a community-based population study, where around 1382 participants were recruited and had telomere length measured. The association of telomere length with C-peptide was studied using multiple linear regression models. We also examined if obesity, measured by body mass index, and inflammation could affect this observed association. Results Around 48% percent of these participants were men and 52% were women. The average ages were 51.7 years old for men and 49.1 years old for women. After controlling for age and sex, one unit increase of telomere length was associated with -0.17(-0.28, -0.06) unit decrease of C-peptide. Additionally controlling for body mass index, the association magnitude was decreased to -0.13(-0.23, -0.04). Further adjusting for inflammation biomarker did not change the effect estimates. Conclusions: Longer telomere was associated with lower levels of C-peptide. This association could be attenuated by adjusting for obesity.